Técnica e política na obra de Vitor Marinho: uma análise teórico-epistemológica - Dias, Leon Ramyssés Vieira (2018)
The productions of the Intellectuals of Physical Education help to understand the different ways of thinking about, as well as the conceptions present in the area throughout history. The study of these productions is also important to understand a little more about these intellectuals, such as the vision of man and world present in their works. In the 1980s, Brazil was undergoing a process of re-signification and struggle for democracy. This scenario has expanded in several areas of society, also permeating Physical Education. One of the intellectuals responsible for introducing critical thinking in the area was Vitor Marinho, who, together with other intellectuals, promoted the breakdown of some paradigms linked to the biologicist and militaristic conception of Physical Education. Vitor Marinho understands the need of teaching the technique in class, but without the teacher leaving the political foundation of his practice. Based on the conception of this intellectual, the present study has as a problem situation to understand the role of technique and politics in the texts of Vitor Marinho. The objective is to analyze the work of the intellectual from the theoreticalepistemological point of view. In order to subsidize the analysis of the study we appropriate the theoretical framework of critical and Marxist cut. The treatment of the data is qualitative. The data regarding the political conception of Vitor Marinho are based on the concept of politics and intellectual of Antonio Gramsci. Already the technique and its questions were thought in the light of Alvaro Vieira Pinto. The epistemological analysis of Vitor Marinho's work allowed us to verify the rupture of the phenomenological philosophical current of thought for historical-dialectical materialism. From this rupture, we compare how technique and politics are manifested in Vitor's work, in addition to other elements such as the conception of man, world and teaching. It was verified that: 1) the theoretical-epistemological change is essential to understand how the technique and the politics are manifested 11 in the work of Vitor Marinho; 2) the technique and the politics in the author's thought approach the conception of polytechnics; 3) Vitor's technical-pedagogical conception does not change with the change of epistemological referential, what changes is the social role that it assumes; 4) from the Marxist perspective, the debate on political issues goes deeper as the debate on technique diminishes; 5) Humanism permeates the entire work of Vitor Marinho, regardless of the theoretical-epistemological moment in which the author finds himself.